Uji Aktivitas Antidiabetes Ekstrak Etanol Daun Babandotan (Ageratum conyzoides L.) pada Mencit Putih (Mus musculus L.) Jantan yang Diinduksi Aloksan - Mira Febrina; Syilfia Hasti; Arnel Nurisma; Nanang Nanang (JURNAL FARMASI DAN MAKANAN, 2023)
Diabetes mellitus is a disease caused by an increased blood glucose level due to insulin deficiency, either absolute or relative. This study aims to determine the antidiabetic activity of the babandotan (Ageratum conyzoides L.) leaves ethanol extract against alloxan-induced male white mice (Mus musculus L.). The inducer used was 175 mg/kgBW of alloxan monohydrate intraperitoneally. The parameters observed were blood glucose level, body weight, 24-hour drinking water volume, and 24-hour urine volume. A total of 30 mice were divided randomly into 6 treatment groups, group 1 served as the normal group, namely mice with blood glucose levels < 200 mg/dL and were only given food or drink, group 2 served as the negative control, that is diabetic mice were given Na CMC 1 %, group 3 served as the positive control, namely diabetic mice that were given 0.65 mg/kgBW of glibenclamide and group 4, 5 and 6 were groups of diabetic mice that were given babandotan leaves ethanol extract doses of 200, 400, and 600 mg/kgBW. The ethanol extract of babandotan leaves was administered once a day for 15 consecutive days. The results showed that the administration of babandotan leaves ethanol extract significantly reduced blood glucose levels (p < 0.05) in diabetic mice, a significant difference in body weight observations (p < 0.05) compared to the negative control, a decreased of 24-hour drinking water volume (p < 0.05) and also a decreased of 24-hour urine volume (p < 0.05).